2016
DOI: 10.1007/s10021-016-9974-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Regime Shift in Nitrogen Export from a Forested Watershed

Abstract: In this study, we document a functional regime shift in stream inorganic nitrogen (N) processing indicated by a major change in N export from a forested watershed. Evidence from 36 years of data following experimental clearcut logging at Coweeta Hydrologic Laboratory, NC, suggests that forest disturbance in this area can cause elevation of dissolved inorganic N (DIN) loss lasting decades or perhaps longer. This elevation of N export was apparently caused by an initial pulse of organic matter input, reduced veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 110 publications
4
40
0
Order By: Relevance
“…Our results and previous studies (e.g., Lutz et al, ; Mulholland & Hill, ) suggest that instream processes play a major role in seasonal patterns of baseflow DIN concentrations (Figure ). We did not see the unimodal, strong summer peak pattern that typically occurs in small forested, headwater streams in this area (Webster, Knoepp, et al, ; Webster, Newbold, & Lin, ). Apparently, there is sufficient springtime light in the third‐order, forested streams included in this study (Ball Creek and Ray Branch) to stimulate algal production and minimize DIN concentration in spring.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Our results and previous studies (e.g., Lutz et al, ; Mulholland & Hill, ) suggest that instream processes play a major role in seasonal patterns of baseflow DIN concentrations (Figure ). We did not see the unimodal, strong summer peak pattern that typically occurs in small forested, headwater streams in this area (Webster, Knoepp, et al, ; Webster, Newbold, & Lin, ). Apparently, there is sufficient springtime light in the third‐order, forested streams included in this study (Ball Creek and Ray Branch) to stimulate algal production and minimize DIN concentration in spring.…”
Section: Discussionmentioning
confidence: 70%
“…The high DIN concentrations of Crawford Branch and perhaps Bates Branch apparently saturated instream uptake, resulting in a single winter peak. This is similar to the results reported by Webster, Knoepp, et al (). Using a 42‐year data set, they showed that a reference stream and prelogging data from another stream both exhibited a strong summer peak in DIN concentration.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In the case of non‐self‐averaging time series, higher‐frequency sampling may not confer any advantage in detecting meaningful trends or predicting future trajectories (Kirchner & Neal, ). More nuanced methods need to be developed, potentially looking for temporal shifts in C‐Q relationships (e.g., Webster, Knoepp, Swank, & Miniat, ) though these too may be affected by long travel times.…”
Section: Discussionmentioning
confidence: 99%